Knowledge and practices of Indonesian rural communities and poultry farmers toward avian flu - Yakhshilikov, Yorbol; Tiongco, Marites; Narrod, Clare; Friedman, Jed (International Food Policy Research Institute, 2009)
Understanding people’s knowledge, attitudes, practices, and perceptions (KAPP) about and toward risk is an important step in determining which cost-effective measure to adopt. It also is important in assessing poor people’s willingness to adopt cost-effective prevention and control measures for reducing the risk of highly pathogenic avian influenza (HPAI). Although studies in several countries indicate some level of awareness about HPAI, practices and attitudes for preventing and controlling HPAI disease spread and outbreaks have not changed (Fielding et al. 2005, Maton et al. 2007, DiGiuseppe et al. 2008, Leslie et al. 2008).